2012
DOI: 10.1227/neu.0b013e31823f5afa
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Management of Vestibular Schwannoma—A Prospective Cohort Study

Abstract: There was a small but statistically significant improvement in vestibular complaints and no change in the occurrence of tinnitus. Except for hearing loss caused by surgery, treatment did not affect symptoms or QOL significantly. Growth was associated with the occurrence of tinnitus and balance problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 26 publications
3
69
1
2
Order By: Relevance
“…12 Importantly, the SF-36, GBI, and PROMIS-10 are multipurpose instruments and therefore are heavily influenced by patient comorbidity and may lack the sensitivity required to detect subtle changes after treatment or small differences between management arms. 4,9,11 In 2010 Shaffer and colleagues introduced the disease-specific PANQOL scale, a 26-item questionnaire evaluating facial function, balance, hearing, pain, anxiety, energy, and general health. Initial evaluation yielded robust face, content, criterion, and construct validity with high test-retest reliability.…”
Section: Discussionmentioning
confidence: 99%
“…12 Importantly, the SF-36, GBI, and PROMIS-10 are multipurpose instruments and therefore are heavily influenced by patient comorbidity and may lack the sensitivity required to detect subtle changes after treatment or small differences between management arms. 4,9,11 In 2010 Shaffer and colleagues introduced the disease-specific PANQOL scale, a 26-item questionnaire evaluating facial function, balance, hearing, pain, anxiety, energy, and general health. Initial evaluation yielded robust face, content, criterion, and construct validity with high test-retest reliability.…”
Section: Discussionmentioning
confidence: 99%
“…11,27 Previous studies have demonstrated that among patients with sporadic VS, ongoing dizziness and headache are associated with the greatest health-related quality of life (HRQOL) reduction, whereas the contributions of unilateral hearing loss, tinnitus, and facial neuropathy are generally less by comparison. [2][3][4]22,26 Despite the substantial physical and emotional burden associated with headache in patients with VS, this condition remains understudied. To our knowledge, no publications have specifically characterized headache in patients with VS receiving SRS or conservative observation.…”
mentioning
confidence: 99%
“…Whitmore et al 39 suggested that conservative management is associated with a significantly higher incidence of functional hearing loss; however, at this point, the comparison of hearing outcomes between conservative management and other forms of therapy is largely inconclusive. 3 The latest prospective study on conservative management by Breivik et al 4 suggested that hearing deteriorates in patients over time, regardless of treatment or tumor growth.…”
Section: Outcomes Of Conservative Managementmentioning
confidence: 99%